2007
DOI: 10.1007/s00268-006-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy and the Outcome of Liver Resection for Colorectal Metastases

Abstract: This study shows no evidence that neoadjuvant chemotherapy, and in particular oxaliplatin, increases the risk associated with liver resection for colorectal metastases. Long-term outcome is reduced in patients receiving preoperative chemotherapy, although they have more advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Some studies suggest a change in the liver parenchyma following chemotherapy: oxaliplatin was associated with an increase in sinusoidal injury [9,10,25,26], whereas irinotecan was associated with an increased risk of steato-hepatitis [10,27,28]. The effect of chemotherapy on early post-operative outcome is still controversial in the literature, especially when results come from retrospective observational studies [9][10][11][12][14][15][16][17][18]. Propensity score analysis can help in reducing the impact of confounding variables, and matching on the propensity score makes it possible to balance measured variables between treated and untreated subjects.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies suggest a change in the liver parenchyma following chemotherapy: oxaliplatin was associated with an increase in sinusoidal injury [9,10,25,26], whereas irinotecan was associated with an increased risk of steato-hepatitis [10,27,28]. The effect of chemotherapy on early post-operative outcome is still controversial in the literature, especially when results come from retrospective observational studies [9][10][11][12][14][15][16][17][18]. Propensity score analysis can help in reducing the impact of confounding variables, and matching on the propensity score makes it possible to balance measured variables between treated and untreated subjects.…”
Section: Discussionmentioning
confidence: 96%
“…makes parenchymal dissection a more hazardous procedure and hemostasis more difficult to achieve, with a consequent expected increase in perioperative morbidity and mortality [9][10][11][12][13]. In the EORTC trial of Nordlinger et al in 2008, an increased occurrence of reversible post-operative complication was reported in patients receiving neo-adjuvant chemotherapy in comparison to patients who were submitted to surgery alone [13], whereas retrospective analyses from various series reported contrasting results [14][15][16][17][18]. These discrepancies are probably the consequence of population selection biases typical of observational retrospective studies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the concern of hepatic failure or other severe associated complications after long-term combination chemotherapy has been alleviated due to a number of recent reports [11,12,[18][19][20][21]. However, the question, if elderly patients can safely tolerate liver surgery after neoadjuvant chemotherapy has not been evaluated yet.…”
Section: Introductionmentioning
confidence: 97%
“…Hepatobiliary surgeons nowadays face two emerging ''populations'' which are eventually considered at risk for perioperative complications, leading to adverse outcome in the long-term [10]: first, the fraction of patients who are aged 70 and older continues to increase and in the future more and more procedures will have to be done in elderly individuals [11]. Secondly, as promising data of trials dealing with the feasibility of neoadjuvant treatment are released, an increasing number of medical and surgical oncologists will consider this option to further optimize patient care and survival [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%